SOFTWARE TENTANG FLEKSIBILITAS ATLET SENAM - Ranu Baskora Aji Putra (Universitas Negeri Semarang, 2014)
Important factor in practicing gymnastics performance was the readiness of children in each session of exercise every day. Internal readiness is a psychological aspects, composed by encouragement, motivation, responsibility, learning intentions and so forth. And external readiness are physical condition prior to the training session. Physical conditions are include body mass, muscle joints readiness, and adjustment of the body to be ready to move on. Gymnastics with characteristic patterns of extreme motion requires a wide range of motion trajectories. And flexibility is one important factor in this sport . Gymnastics coach should be very careful in monitoring the development and growth of their athletes . Gymnastics coach should closely monitor the development and growth of its athletes. Monitoring can be done through the implementation of an exercise program checks every day, including the fit between implementation and readiness of the athletes physical condition. Through data processing techniques on the physical condition of athletes before practicing gymnastics, coach will be easy to determine the readiness of the athletes in training in each training session. While providing action efforts based on existing data. This study describes the use of a simple database tests readiness and flexibility for monitoring athletes in gymnastics.